2021
DOI: 10.1021/acs.jmedchem.1c01066
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Optimization of Orally Bioavailable Phthalazone and Cinnolone Carboxylic Acid Derivatives as S1P2 Antagonists against Fibrotic Diseases

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic and progressive lung disease. Current treatments only slow down disease progression, making new therapeutic strategies compelling. Increasing evidence suggests that S1P2 antagonists could be effective agents against fibrotic diseases. Our compound collection was mined for molecules possessing substructure features associated with S1P2 activity. The weakly potent indole hit 6 evolved into a potent phthalazone series, bearing a carboxylic acid, with the aid of a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…, lymphoid tissues and spleen) . Over the past few years, S1PR2 has been identified as a potential therapeutic target and S1PR2 antagonists were developed as therapeutic agents for the treatment of inflammation, multiple sclerosis (MS), and fibrotic diseases, representative structures are shown in Figure . JTE-013 is the first reported S1PR2 antagonist and has been widely used in defining the biological roles of S1PR2 in various disease . In our previous study, JTE-013 showed promising 5-FU-resistance reversal activity in primary 5-FU-resistant HCT116 DPD cells, whereas it exhibited moderate effect in SW620/5-FU cells, which acquired its resistance from the continuous treatment of 5-FU .…”
Section: Introductionmentioning
confidence: 99%
“…, lymphoid tissues and spleen) . Over the past few years, S1PR2 has been identified as a potential therapeutic target and S1PR2 antagonists were developed as therapeutic agents for the treatment of inflammation, multiple sclerosis (MS), and fibrotic diseases, representative structures are shown in Figure . JTE-013 is the first reported S1PR2 antagonist and has been widely used in defining the biological roles of S1PR2 in various disease . In our previous study, JTE-013 showed promising 5-FU-resistance reversal activity in primary 5-FU-resistant HCT116 DPD cells, whereas it exhibited moderate effect in SW620/5-FU cells, which acquired its resistance from the continuous treatment of 5-FU .…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, another series of phthalazone and quinolone carboxylic acid analogs was reported by Mammoliti and coworkers from weak fragment hits through a structure-based design strategy (Figure 20). 132 In the beginning, they analyzed the substructure features in reported S1PR2 antagonists and agonists and found that two types of skeleton structure, including diaryl ketone and diaryl amide, were recurring. Consequently, they searched their compound collection containing these two structures, and identified compound 37 as a novel S1PR2 antagonist hit with modest S1PR2 antagonist activity (IC 50 > 8 μM) in the Ca 2+ assay in hS1PR2-overexpressing CHO cells.…”
Section: Phthalazone and Quinolone Carboxylic Acid Analogsmentioning
confidence: 99%
“…[4] 5-Pyridonyl-indazole derivative exhibits good sphingosine-1-phosphate receptor 2 (S1P2) inhibitory activity and in vivo anti-idiopathic pulmonary fibrosis potency. [5] The N-myristoyl transferase inhibitors with this scaffold achieve the full cures in a mouse model of African sleeping sickness. [6] Owing to their importance, the direct functionalization of 2H-indazoles becomes highly desirable to medicinal chemistry and organic chemistry.…”
Section: Introductionmentioning
confidence: 99%